Carbon Nanofiber-Based Functional Nanomaterials for Sensor Applications - Wang, Zhuqing (Nanomaterials (Basel), 2019)
Carbon nanofibers (CNFs) exhibit great potentials in the fields of materials science, biomedicine, tissue engineering, catalysis, energy, environmental science, and analytical science due to their unique physical and chemical properties. Usually, CNFs with flat, mesoporous, and porous surfaces can be synthesized by chemical vapor deposition and electrospinning techniques with subsequent chemical treatment. Meanwhile, the surfaces of CNFs are easy to modify with various materials to extend the applications of CNF-based hybrid nanomaterials in multiple fields. In this review, we focus on the design, synthesis, and sensor applications of CNF-based functional nanomaterials. The fabrication strategies of CNF-based functional nanomaterials by adding metallic nanoparticles (NPs), metal oxide NPs, alloy, silica, polymers, and others into CNFs are introduced and discussed. In addition, the sensor applications of CNF-based nanomaterials for detecting gas, strain, pressure, small molecule, and biomacromolecules are demonstrated in detail. This work will be beneficial for the readers to understand the strategies for fabricating various CNF-based nanomaterials, and explore new applications in energy, catalysis, and environmental science.